Risk factors for childhood pneumonia: a case-control study in a high prevalence area in Indonesia - Vivi Ninda Sutriana; Mei Neni Sitaresmi; Abdul Wahab (The Korean Pediatric Society, 2021)
Background Acute respiratory infections (ARIs), especially pneumonia, remain a major cause of infant mortality worldwide. In Indonesia, pneumonia is the second most common cause of infant and toddler deaths. Exclusive breastfeeding and basic immunization can protect infants and children from contracting pneumonia. Purpose Our goal was to assess the risk factors for childhood pneumonia in regions with a high prevalence of pneumonia in Indonesia. Methods This case-control study was conducted between March and April 2019. A total of 176 infants and toddlers aged 10-59 months were enrolled and selected from among patients who visited the community health center. Cases of pneumonia were diagnosed clinically based on the World Health Organization guidelines, and the control was nonpneumonia. Results The risk factors for the diagnosis of pneumonia included no or nonexclusive breastfeeding (odds ratio [OR], 7.95; 95% confidence interval [CI], 3.52-17.94), incomplete basic immunizations (OR, 4.47; 95% CI, 2.22-8.99), indoor air pollution (OR, 7.12; 95% CI, 3.03-16.70), low birth weight (OR, 3.27; 95% CI, 1.19-8.92), and a high degree of wasting (OR, 2.77; 95% CI, 1.06-7.17). Other variables such as nutritional status (height-for-age z score), age, sex, and educational status of the mother were not risk factors for pneumonia. Conclusion No or nonexclusive breastfeeding, incomplete basic immunizations, indoor air pollution, a history of low birth weight, and severe malnutrition were risk factors for childhood pneumonia. Breastfeeding was the dominant factor, while sex modified the relationship between exclusive breastfeeding and the incidence of pneumonia.